PENGARUH ARUS KAS OPERASI DAN MODAL KERJA BERSIH TERHADAP LABA BERSIH PADA PT. KALBE FARMA TBK. - Della Maretha; Putri Ayu Rimanda Rizky (Jurnal Manajemen FE-UB, 2020)
The research aims to analyze whether operating cash flow and net working capital have aneffect on net income. The data used in this research are secondary data and the selection ofresearch samples using purposive sampling method. The sample of this research is PT KalbeFarma Tbk for the period 2011-2018 with quarterly data (32 financial reports). This researchanalysis method uses multiple linear analysis using Eviews8 software.The results showed that simultaneously operating cash flow and net working capitalvariables had a significant effect on net income. Partially, operating cash flow and net workingcapital have a significant and significant effect on net income.